Patients with medical risk factors for chronic kidney disease are at increased risk of renal impairment despite the use of nephron‐sparing surgery. (30th March 2015) - Satasivam, Prassannah; Reeves, Fairleigh; Rao, Kenny; Ivey, Zacchary; Basto, Marnique; Yip, Marcus; Roth, Hedley; Grummet, Jeremy; Goad, Jeremy; Moon, Daniel; Murphy, Declan; Appu, Sree; et al.
<x xml:space="preserve">Abstract</x> Objective To determine whether patients with normal preoperative renal function, but who possess medical risk factors for chronic kidney disease (CKD), experience poorer renal function after partial nephrectomy (PN) for renal cell carcinoma (RCC) compared with those without risk factors. Patients and Methods The effects of age, hypertension (HTN) and diabetes mellitus (DM) on estimated glomerular filtration rate (eGFR) were investigated in 488 consecutive operations for RCC performed during 2005–2012 at six Australian tertiary referral centres; 156 patients underwent PN and 332 patients underwent radical nephrectomy (RN). We used chi‐squared test and binary logistic regression to analyse new‐onset CKD, and multiple linear regression to investigate determinants of postoperative eGFR. Results The development of new‐onset eGFR of <60 mL/min was related to undergoing RN rather than PN (risk ratio [RR] 2.7, P < 0.001), older age (RR 1.6, P < 0.001) and the presence of HTN (RR 1.6, P = 0.001) and DM (RR 1.5, P = 0.003). Patients undergoing PN were still at risk of new‐onset CKD if medical risk factors were present. Whereas 7% of patients undergoing PN without CKD risk factors developed new‐onset eGFR <60 mL/min, this figure increased to 24%, 30% and 42% for older age, HTN and DM, respectively. Patients with eGFR of 45–59 mL/min were more likely to progress to more severe forms of CKD and end‐stage renal failure than those with eGFR of ≥60 mL/min. On multivariate analysis, RN, rather than PN, age and the presence of DM (but not HTN), predicted both the development of new‐onset eGFR of <60 mL/min (R2 = 0.37) and new‐onset eGFR <45 mL/min (R2 = 0.42). Conclusion Patients with medical risk factors for CKD are at increased risk of progressive renal impairment despite the use of PN. Where feasible, nephron‐sparing surgery should be considered for these patients.